Occurrence of Pedunculate Barnacle, Octolasmis spp. in Blue Swimming Crab, Portunus pelagicus [Tingkat Kejadian Pedunculate Barnacle, Octolasmis spp. pada Rajungan, Portunus pelagicus] - Marina hasan; Mohd Fazrul Hisam Abd Aziz; Kismiyati Kismiyati; Sri Subekti; Mohd Ihwan Zakariah (Faculty of Fisheries and Marine Universitas Airlangga, 2019)
AbstractBarnacles are symbiont and harm to the crabs when they are in large numbers. They will affect the respiration, normal activity and growth of the crabs. The prevalence, mean intensity and identification of pedunculate barnacle, Octolasmis spp. on blue swimming crab, Portunus pelagicus from the coastal area of Kuala Terengganu were studied. The site specificity of the different species of Octolasmis attached was examined. The crabs were measured and weight. The crabs were euthanized by put in ice until no movement. The Octolasmis were observed from the surfaces and gills or brachial chamber. The Octolasmis were observed from each gill. The prevalence and mean intensity was calculated. The Octolasmis were preserved in 70% alcohol and mounting using glycerine jelly to make the permanent slide. A total of all 13 crabs were infested by four species of Octolasmis which is 218 Octolasmis angulata, 191 Octolasmis warwickii, 16 Octolasmis tridens and 218 Octolasmis lowei. Octolasmis angulate showed the highest prevalence (84.62%) and lowest prevalence was O. lowei (23.08%) and O. warwickii (23.08%). The barnacles were attached to the gill, carapace, abdomen and also walking legs. Barnacle occurred most frequently on the gill part by having 371 (57.70%) barnacles compared to other areas, 272 (42.30%) barnacles. The distributions of barnacle in this study suggest distal areas are more susceptible in infestation by Octolasmis spp. However, they did not show site specificity on the gill areas because it depends on the water current.AbstrakBarnacle (teritip) adalah simbion yang dalam jumlah besar akan membahayakan kepiting. Teritip tersebut berpengaruh pada pernapasan, aktivitas normal dan pertumbuhan kepiting. Prevalensi, intensitas rata-rata dan identifikasi pedunculate barnacle, Octolasmis spp. pada rajungan, Portunus pelagicus dari daerah pesisir Kuala Terengganu telah diteliti. Kekhasan lokasi dari berbagai spesies Octolasmis telah diperiksa. Kepiting telah diukur dan ditimbang. Kepiting dieuthanasi dengan cara dimasukkan kedalam es sampai tidak bergerak. Octolasmis diamati dari permukaan tubuh dan insang (branchial chamber). Octolasmis diamati pada tiap insang. Prevalensi dan intensitas rata-rata dihitung. Octolasmis diawetkan dalam alcohol 70 % dan mounting menggunakan Jeli gliserin untuk membuat slide permanen. Semua kepiting 13 ekor telah terinfestasi oleh empat spesies Octolasmis, yaitu 218 Octolasmis angulata, 191 Octolasmis warwickii, 16 Octolasmis tridens dan 218 Octolasmis lowei. Octolasmis angulate menunjukkan prevalensi paling tinggi (84,62%) dan prevalensi paling rendah adalah O. lowei (23,08%) dan O. warwickii(23,08%). Teritip menyerang insang, karapas, abdomen dan juga kaki jalan.Teritip paling sering ditemukan pada bagian insang 371 ekor (57,70%) dibandingkan pada bagian lain, 272 ekor (42,30%). Distribusi teritip pada penelitian ini menunjukkan bahwa bagian distal lebih rentan mengalami infestasi Octolasmis spp. Namun, teritip tidak menunjukkan kekhasan lokasi pada daerah insang bergantung pada arus air.